EXPLORING THE GLOBAL IMPACT OF CHATGPT IN HIGHER EDUCATION FROM STUDENTS PERSPECTIVE - Aristovnik, Aleksander (PEOPLE: International Journal of Social Sciences, 2024)
The introduction of ChatGPT in November 2022 marked a pivotal moment in AI’s role in higher education, sparking a mix of excitement and skepticism among educators and researchers. This advanced AI’s ability to simulate human-like conversations and provide informative responses has led to its exploration for enhancing learning experiences across various disciplines, including public administration. However, this exploration is tempered by concerns over issues like AI bias, data privacy, and the implications of increased reliance on AI technologies in educational settings. Emphasis on the differences between these fields in terms of AI application and impact will be explored and analyzed. The paper details the "Students’ Perception of ChatGPT" survey conducted by the Faculty of Public Administration at the University of Ljubljana and an international consortium, which garnered over 23,000 responses globally. The survey investigated ChatGPT’s influence on students’ learning experiences, academic performance, skill development (such as critical thinking and writing), emotional responses, and ethical perspectives on AI in education. Utilizing a detailed questionnaire format, the survey combined both quantitative and qualitative methods to capture diverse student interactions and perceptions of ChatGPT. The findings are anticipated to shed light on ChatGPT’s transformative role in education, examining its potential in areas like tutoring, collaborative learning, and language skill development. Additionally, the survey aims to explore students’ motivations and engagement in learning processes influenced by ChatGPT, while also addressing the challenges and concerns related to its use, such as accuracy and potential misuse. Finally, the paper seeks to contribute to the ongoing dialogue about AI’s role in education by providing a comprehensive view of global student perspectives on ChatGPT. The insights gained are expected to be instrumental for educators, policymakers, and AI developers in understanding and navigating the complex landscape of AI in higher education, thereby shaping future educational strategies and applications. The added focus on the differences among various academic fields will further enrich this understanding, offering a nuanced view of how ChatGPT’s impact varies across disciplines.